Development of a Model for the Construction of Corporate Manuals with QR Codes - Borja-Galeas, Carlos (2023)
The creation of a brand manual that includes QR triggers makes it possible to unify and update the traditional editorial design with new technologies. The present study exposes a construction model of these corporate identity manuals and all the processes that must be carried out to obtain positive results in their application. The unit of analysis of this research was developed with three brand manuals from companies in the city of Quito, to which augmented reality QR triggers were included, which allowed access to complementary audiovisual material that helps the suppliers of these companies to use and apply the mark appropriately.